Sleep disturbance and brain health in professional association footballers - Howarth, N. E.; Miller, M. A.; Batten, J.; Ji, C.; Dawes, H.; Grey, M. J.; Pearce, A. J.; White, A. J. (Frontiers in Sports and Active Living, 2025)
Introduction: Sleep is a critical component of normal bodily function as well as for peak performance in athletes. This study examined the associations between quality and quantity of sleep, sleep disturbances, head injuries, and headaches in current and former association football (soccer) players in the United Kingdom (UK). Methods: An anonymous online cross-sectional survey was sent to members of the Professional Footballers' Association with questions relating to sleep, concussion history, and headaches. Results: The survey was completed by 600 participants (18 women, 582 men; aged 17-92 years, mean age 44.12 years ± 15.33 SD), comprising 195 current and 405 retired players. Significant clinical sleep disruption was reported in 17.0% of participants, with 22.5% achieving six hours or less of sleep per night. Odds ratios (OR) demonstrated that sleep disruption was associated with headaches [2.66 OR, 95% Confidence Interval (CI): 1.61-4.38; p < 0.001], suspected concussions (1.84 OR, 95% CI: 1.03-3.36; p = 0.040), and short sleep (4.06 OR, 95% CI: 2.56-6.44; p < 0.001). Both diagnosed and suspected concussions were significantly associated with waking up feeling tired or worn out (diagnosed: p = 0.019; suspected: p < 0.001). Discussion: A large proportion of former and current footballers experience clinically significant sleep disturbance, which is significantly associated with headaches and concussion history. Further research is needed to explore the long-term relationship between brain health and sleep in this population.